(untitled) (Medico Legal Update, 2020)
(VAP) is defined as pneumonia that develops in mechanically ventilated patients after 48 hours or more of mechanical ventilator support, VAP increases the mortality and morbidity rates of patients and healthcare costs, This study was a descriptive cross-sectional survey. Sample a total sample of 126 nurses was collected for the current study,setting and Participants a convenience sample of graduate nurses was obtained from eight hospitals throughout Babylon. The study was approved by the ethics committees of the Babylon health department and the participating, Researcher used standard a questionnaire that integrated the assessment of nurse’s knowledge for prevention of VAP from the Center of Disease Control and Prevention questionnaire was validated by a panel of four specialists in the disciplines of nursing, The questionnaire was administered to the participants in their hospitals by the principle investigator. Nurses were informed that their completion of the questionnaire would be considered as consent to participate.SPSS version 22 was used for data analysis, The study conclude that the mean age of participants in the study was young and female, the majority of the nurses didn’t know that the mechanical ventilator humidifier must be changed weekly to prevent VAP. Researcher encourage all Iraqihospitals ICUs nurses to involve inclinical training to improve nurses acquisition and to evaluate the content of the nursing curricula to identify shortcomings in content. It is imperative that VAP-prevention guidelines be integrated in training and teaching within the nursing schools, and that the content and teaching strategies of infection control courses are updated.